Characterization of a glucansucrase from Lactobacillus reuteri E81 and production of malto-oligosaccharides - Ispirli, Humeyra; Yuzer, Mustafa Onur; Skory, Christopher; Colquhoun, Ian J.; Sagdic, Osman; Dertli, Enes (TAYLOR & FRANCIS LTD, 2019)
Glucansucrases, which can be produced by different Lactic Acid Bacteria (LAB), catalyze the synthesis of alpha-glucans with different structures and properties using sucrose as substrate. In this study, a novel glucansucrase (GTFA) from Lactobacillus reuteri E81 was identified and heterologously expressed. Alignments of GTFA with other glucansucrases revealed its novelty and a putative 3D model structure was obtained. The biochemical properties of the truncated enzyme without the N-terminal variable region, GTFA-Delta N, was characterized. The K-m and V-max were found to be 7.5 mM and 1.49 IU/mg, respectively, and it showed optimum activities at pH 7 and at 50 degrees C. The GTFA-Delta N produced in vitro an alpha-glucan with (alpha 1 -> 3) and (alpha 1 -> 6) glycosidic linkages using sucrose as the substrate. Importantly, GTFA-Delta N synthesized DP = 9 oligosaccharides using sucrose and maltose as the donor and acceptor sugars, respectively, as detected by TLC, HPLC, LC-MS and NMR analysis.
Keywords: Glucansucrase; glucan; malto-oligosaccharides; MOLECULAR CHARACTERIZATION; STRUCTURAL-CHARACTERIZATION; DEXTRANSUCRASE EFFICIENT; OLIGOSACCHARIDES; ENZYMES; SOURDOUGH; REUTERANSUCRASE; EXPRESSION; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology